Rancang Bangun Meja Packaging Susu di CV. Memory Susu Nusantara Semarang Melalui Pendekatan Anthropometri - Yohanes, Antoni; Ekoanindiyo, Firman Ardiansyah; Radyanto, Mohammad Riza; Al Amin, Imam Husni (Fakultas Teknik Universitas Tulang Bawang, 2025)
The milk packaging table at CV Memory Susu Nusantara Semarang city is still sober. There are many weaknesses in working manually that cause work to slow down and get tired quickly. Adding facilities to the milk production process at CV Memory Susu Nusantara Semarang city in the form of a milk packaging table that makes it easier to work. The plan uses anthropometric methods with a sample of employees and the surrounding community with a total of 30 people as the size. The measurements used are hand reach forward, hip height, standing shoulder height and shoulder width. The research produced a table size according to anthropometric data, namely table height 80 cm, table area width 50 cm, reach length to the table 60 cm, seat height to the table 46 cm. It can be concluded that later with the packaging table facility workers are more comfortable at work, besides that it is more effective than the previous traditional way. Keywords: Anthropometry, design, packaging, table